2014
DOI: 10.1021/jf502486q
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Cereals and Pulses: Health Implications in Bangladesh

Abstract: This research was conducted to evaluate the concentration of seven common heavy metals (Cr, Ni, Cu, Zn, As, Cd, and Pb) in cereals and pulses and associated health implications in Bangladesh. USEPA deterministic approaches were followed to assess the carcinogenic risk (CR) and noncarcinogenic risk which was measured by target hazard quotient (THQ) and hazard index (HI). Total THQ values for As and Pb were higher than 1, suggesting that people would experience significant health risks if they ingest As and Pb f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 34 publications
3
41
2
Order By: Relevance
“…A previous study by Roychowdhury et al [14] reported similar mean Cu concentration in wheat of 0.378 mg/100 g cultivated in the western part of India. In agreement with the findings of the present study, the other study, [15] reported similar total Cu content, in rice (0.17 mg/100 g) and maize (0.23 mg/100 g). The data for Cu content in wheat (0.37 mg/100 g) are in agreement with the data published by Srikumar.…”
Section: Cu Content and Bioaccessibility From Cereals And Pulsessupporting
confidence: 94%
See 1 more Smart Citation
“…A previous study by Roychowdhury et al [14] reported similar mean Cu concentration in wheat of 0.378 mg/100 g cultivated in the western part of India. In agreement with the findings of the present study, the other study, [15] reported similar total Cu content, in rice (0.17 mg/100 g) and maize (0.23 mg/100 g). The data for Cu content in wheat (0.37 mg/100 g) are in agreement with the data published by Srikumar.…”
Section: Cu Content and Bioaccessibility From Cereals And Pulsessupporting
confidence: 94%
“…The Cr concentrations found in cereals and pulses was thus similar. In our study, the mean Cr concentration in rice, wheat and maize was 0.06, 0.056, and 0.08 mg/100 g. Mean Cr concentration in Bangladeshi rice, wheat and maize was reported to be 0.18, 0.13, and 0.19 mg/100 g, [15] which is higher than our values. However, Fu et al [28] reported mean Cr concentration in Chinese rice to be 0.02 mg/100 g. In the present study, the highest Cr concentration among all cereals and pulses was found in black gram (0.11 mg/100 g).…”
Section: Cr Content and Bioaccessibility From Cereals And Pulsescontrasting
confidence: 86%
“…The variety with the lowest total Cu content was Bomba (1.45 mg/kg; see Table 3). These values are in agreement with those reported by previous research such as 0.50-3.3 mg/kg (Islam, Ahmed, & Habibullah-Al-Mamun, 2014) and 1.90 mg/kg (Kumari & Platel, 2017).…”
Section: Coppersupporting
confidence: 94%
“…It is used at health risk assessment in order to determine the carcinogenicity of the samples (Islam et al, 2014). The formula below suggested by Chien et al (2002) …”
Section: Determination Of Target Hazard Quotientmentioning
confidence: 99%